2006
DOI: 10.1080/00480169.2006.36716
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that moxidectin is a greater risk factor than ivermectin in the development of resistance to macrocyclic lactones by Ostertagia spp in sheep in south eastern Australia

Abstract: Use of MOX for > or =2 of the preceding 5 years was associated with a higher prevalence of resistance to ML by Ostertagia spp on sheep farms in south eastern Australia than the use of IVO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 26 publications
2
19
0
Order By: Relevance
“…However, as the anthelmintic concentration slowly subsides to sub-lethal concentrations, both homozygousand heterozygous-resistant parasites are able to establish within the host, while homozygous-susceptible parasites still cannot establish, thereby accelerating the development of AHR (Sutherland and Scott, 2010). While several studies have investigated the role of long-acting formulations as a putative risk factor for AHR (Le Jambre et al, 1999;Sutherland et al, 2000;Leathwick et al, 2006;Rendell et al, 2006;Hughes et al, 2007), only two studies were suitable for quantitative data extraction and synthesis (Rendell et al, 2006;Hughes et al, 2007); the pooled estimate showed a marginally significant positive association between the use of long-acting formulations (either as moxidectin or macrocyclic lactone capsules) and AR (Fig. 5).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…However, as the anthelmintic concentration slowly subsides to sub-lethal concentrations, both homozygousand heterozygous-resistant parasites are able to establish within the host, while homozygous-susceptible parasites still cannot establish, thereby accelerating the development of AHR (Sutherland and Scott, 2010). While several studies have investigated the role of long-acting formulations as a putative risk factor for AHR (Le Jambre et al, 1999;Sutherland et al, 2000;Leathwick et al, 2006;Rendell et al, 2006;Hughes et al, 2007), only two studies were suitable for quantitative data extraction and synthesis (Rendell et al, 2006;Hughes et al, 2007); the pooled estimate showed a marginally significant positive association between the use of long-acting formulations (either as moxidectin or macrocyclic lactone capsules) and AR (Fig. 5).…”
Section: Discussionmentioning
confidence: 96%
“…Another factor frequently investigated was the use of long-acting anthelmintic drugs (Le Jambre et al, 1999;Sutherland et al, 2000;Leathwick et al, 2006;Rendell et al, 2006;Hughes et al, 2007). These drugs have a persistent action, either because of an innate drug characteristic (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While Ostertagia spp are implicated as the parasite most likely to be resistant to ML, it is by no means the only genus involved, as shown similarly by Hughes and McKenna (2005) (Rendell et al 2006).…”
Section: Prevalence Of Anthelmintic Resistance In Undifferentiated mentioning
confidence: 77%